An account of the male and female factor in Chilean cinema (2000-2016) - Hudson Frías, Eileen (2019)
This research deals with the construction of the feminine and masculine in contemporary Chilean cinema (2000-2016). Through a mixed content analysis, demographic and social characteristics of all the characters that had at least one line of dialogue (N = 684) were codified in a corpus composed of the 33 films that achieved more than 100,000 spectators. The incidence of the sex variable was analyzed in the construction of the dramatic objective of the men and women present in the story of the Chilean audiovisual fiction and it was verified that the mediation that the cinema has exercised during this time recreates and maintains the stereotypes of gender that Chilean society currently suffers.